2011
DOI: 10.1002/eji.201040877
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance induction towards cardiac allografts under costimulation blockade is impaired in CCR7‐deficient animals but can be restored by adoptive transfer of syngeneic plasmacytoid dendritic cells

Abstract: Deficiency of transplant recipients for the chemokine receptor CCR7 was originally described to slightly increase the survival time of vascularized solid organ grafts, probably due to a reduced priming of alloreactive T cells. Using a model of allotolerance induction by donorspecific splenocyte transfusion (DST) in combination with anti-CD40L mAb-mediated costimulation blockade (CSB), we show here a striking failure of CCR7-deficient (CCR7 À/À ) recipients to tolerate cardiac allografts. Furthermore, in additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Last, CCR7 is known to be involved in the localization of both DCs and T cells in the T-cell-rich zones of the LNs, indicating a role for CCR7 in T-cell homing and priming (Hopken et al 2004). Recently, Liu et al (2011) showed that a lack of CCR7 prevented tolerance induction in a cardiac murine model of transplantation. This impairment of tolerance was partially rescued by adoptive transfer of wild-type plasmacytoid DCs to the CCR7-deficient mice (Liu et al 2011).…”
Section: Chemokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Last, CCR7 is known to be involved in the localization of both DCs and T cells in the T-cell-rich zones of the LNs, indicating a role for CCR7 in T-cell homing and priming (Hopken et al 2004). Recently, Liu et al (2011) showed that a lack of CCR7 prevented tolerance induction in a cardiac murine model of transplantation. This impairment of tolerance was partially rescued by adoptive transfer of wild-type plasmacytoid DCs to the CCR7-deficient mice (Liu et al 2011).…”
Section: Chemokinesmentioning
confidence: 99%
“…Recently, Liu et al (2011) showed that a lack of CCR7 prevented tolerance induction in a cardiac murine model of transplantation. This impairment of tolerance was partially rescued by adoptive transfer of wild-type plasmacytoid DCs to the CCR7-deficient mice (Liu et al 2011).…”
Section: Chemokinesmentioning
confidence: 99%
“…These specialized vessels are lined abluminally with basement membrane stromal fibers. HEVs are luminally lined with blood endothelial cells (BECs) expressing the CD62L ligand peripheral node addressin (PNAd), which mediates the tethering and rolling of T cells (5,17). T cell arrest on the endothelium is mediated by CCR7 and CXCR4 recognition of CCL21 and CXCL12, respectively, and these chemokines decorate the luminal surface of the HEV.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the level at which administered DCs successfully reach their intended final destination is low. The chemokine receptor CCR7, which mediates migration of tolDCs to lymph nodes in vivo, is thought to be critical in this respect [20,21]. Moreover, the tolDCs should also be capable of migrating to the specific tissues where autoimmunity occurs.…”
mentioning
confidence: 99%